Improving the Reading Comprehension of Eighth-Grade Students through the Scaffolded Reading Method: A Classroom Action Research at MTs Muhammadiyah Kota Gorontalo - Bonde Sabina Andini; Alvons Habibie (English Education Department, 2026)
Reading comprehension is a foundational competence for academic success in English as a foreign language, yet many Indonesian junior secondary students continue to struggle with understanding English texts. This study aimed to improve the reading comprehension of eighth-grade students at MTs Muhammadiyah Kota Gorontalo through the implementation of the scaffolded reading method. The study employed classroom action research following the Kemmis and McTaggart model, conducted in two cycles of three meetings each and involving 18 students (nine male, nine female). Data were collected through multiple-choice reading comprehension tests (pre-test and post-tests), teacher and student observation sheets, and interviews, and were analyzed using descriptive quantitative and qualitative techniques against a success criterion of 70% classical completeness (KKM = 70). The results showed a consistent improvement across phases: the mean score rose from 56.1 in the pre-test (16.7% of students reaching the KKM) to 66.1 after Cycle I (55.6%) and 75.6 after Cycle II (83.3%), exceeding the success criterion. Scaffolding techniques—teacher modeling through read-alouds, shared and guided reading, structured group discussion of narrative texts, vocabulary journaling, and the use of picture storybooks—progressively increased student engagement and independence in comprehending texts. It can be concluded that the scaffolded reading method is effective in improving the reading comprehension of eighth-grade students, and its staged release of responsibility offers a practical framework that English teachers can adopt in comparable madrasah contexts.